Peripheral follicular helper T cells in acute viral diseases: a perspective on dengue. (6th March 2019) - Sánchez-Vargas, Luis A; Mathew, Anuja
Follicular helper T cells (TFH ) are a predominant subset of CD4 + T cells specialized in providing help to B cells in germinal centers and necessary to generate T cell-dependent antibody responses. Peripheral TFH (pTFH ) are the counterpart of TFH found in the circulation, which resemble TFH in many aspects of their phenotype and function. The CD4 + pTFH subset has received a lot of interest recently because they are easy to access and have the potential to serve as a biomarker for long-lasting humoral immunity. This review will discuss recent findings of pTFH in human acute viral diseases with a focus on dengue infection.